2022
DOI: 10.1002/cctc.202200254
|View full text |Cite
|
Sign up to set email alerts
|

Precisely Tailoring Selectivity via Target Group's Steered Adsorption on Cu2O/Tantalate Catalysts for Hydrogenation of 3‐Nitrostyrene

Abstract: The selective hydrogenation of nitroarenes bearing competitive reducible groups to produce functionalized amino compounds has wide application in industrial production. However, to control only reducing the target group is still a challenge. Here, Cu 2 O/M 2 Ta 2 O 6 (M=H, Li, Na, K, Ag, Bi) catalysts were prepared to evaluate their catalytic performance using 3-nitrostyrene (3-NS) as a model reaction. The results confirm pristine Cu 2 O has a highly activity to hydrogenate 3-NS but low selectivity with the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…The catalyst support plays the role of dispersing the metal on its surface, and thus it is critical to both the activity and the selectivity of the targeted selective hydrogenation . Previously, we confirmed that the tantalate component could well promote the selectivity of target groups in this type of catalytic transfer hydrogenation reaction . In addition, a large number of basic sites are present in KTaO 3 , which will facilitate the selective adsorption of –CO groups. , Combined with a series of advantages of tantalate, such as robustness, readily availability, relative inexpensiveness, and lower toxicity, KTaO 3 was selected in this investigation.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…The catalyst support plays the role of dispersing the metal on its surface, and thus it is critical to both the activity and the selectivity of the targeted selective hydrogenation . Previously, we confirmed that the tantalate component could well promote the selectivity of target groups in this type of catalytic transfer hydrogenation reaction . In addition, a large number of basic sites are present in KTaO 3 , which will facilitate the selective adsorption of –CO groups. , Combined with a series of advantages of tantalate, such as robustness, readily availability, relative inexpensiveness, and lower toxicity, KTaO 3 was selected in this investigation.…”
Section: Introductionmentioning
confidence: 69%
“…1 Previously, we confirmed that the tantalate component could well promote the selectivity of target groups in this type of catalytic transfer hydrogenation reaction. 24 In addition, a large number of basic sites are present in KTaO 3 , which will facilitate the selective adsorption of −C�O groups. 25,26 Combined with a series of advantages of tantalate, such as robustness, readily availability, relative inexpensiveness, and lower toxicity, 27 ■ EXPERIMENTAL SECTION Chemicals and Materials.…”
Section: ■ Introductionmentioning
confidence: 99%